Provision of the progestogen-only pill by community pharmacies as bridging contraception for women receiving emergency contraception: the Bridge-it RCT. - Cameron, Sharon T (Health Technol Assess, 2021)
INTRODUCTION: Unless women start effective contraception after using emergency contraception, they remain at risk of unintended pregnancy. Most women in the UK obtain emergency contraception from community pharmacies that are unable to provide ongoing contraception (apart from barrier methods which have high failure rates). This means that women need an appointment with a general practitioner or at a sexual and reproductive health clinic. We conducted a pragmatic cluster randomised cohort crossover trial to determine whether or not pharmacist provision of a bridging supply of a progestogen-only pill plus the invitation to attend a sexual and reproductive health clinic resulted in increased subsequent use of effective contraception (hormonal or intrauterine). METHODS: Twenty-nine pharmacies in three UK cities recruited women receiving emergency contraception (levonorgestrel). In the intervention, women received a 3-month supply of the progestogen-only pill (75 µg of desogestrel) plus a card that provided rapid access to a local sexual and reproductive health clinic. In the control arm, pharmacists advised women to attend their usual contraceptive provider. The primary outcome was reported use of an effective contraception (hormonal and intrauterine methods) at 4 months. Process evaluation was also conducted to inform any future implementation. RESULTS: The study took place December 2017 and June 2019 and recruited 636 women to the intervention (n = 316) and control groups (n = 320). There were no statistically significant differences in demographic characteristics between the groups. Four-month follow-up data were available for 406 participants: 63% (198/315) of the control group and 65% (208/318) of the intervention group. The proportion of participants reporting use of effective contraception was 20.1% greater (95% confidence interval 5.2% to 35.0%) in the intervention group (58.4%, 95% confidence interval 48.6% to 68.2%) than in the control group (40.5%, 95% confidence interval 29.7% to 51.3%) (adjusted for recruitment period, treatment arm and centre; p = 0.011). The proportion of women using effective contraception remained statistically significantly larger, when adjusted for age, current sexual relationship and history of past use of effective contraception, and was robust to the missing data. There were no serious adverse events. CONCLUSION: Provision of a bridging supply of the progestogen-only pill with emergency contraception from a pharmacist and the invitation to a sexual and reproductive health clinic resulted in a significant increase in self-reported subsequent use of effective contraception. This simple intervention has the potential to prevent more unintended pregnancies for women after emergency contraception. TRIAL REGISTRATION: Current Controlled Trials ISRCTN70616901. FUNDING: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 25, No. 27. See the NIHR Journals Library website for further project information.